Reproductive biology, feeding habits and population dynamics of Miyakella nepa latreille - Zainudin, Zamri (2015)
The reproductive biology, feeding habits, and population dynamics of Miyakella nepa (Latreille, 1828) was studied in the coastal waters of Pantai Remis, Perak from February 2012 to January 2013. A total of 951 specimens comprising 565 females and 386 males of M. nepa were examined. The results indicated that the overall male to female ratio of M. nepa was 1:1.46. About 30 M. nepa females were examined every month for their ovarian stages and gonadosomatic index (GSI). The peak GSI for female M. nepa were recorded during March-April, between June and September and November-December during the study period. The maximum GSI value of was 5.8 was observed in July 2012. It was found that M. nepa breed continuously throughout the year. The highest peak of the relative condition factor (Kn) for male and female M. nepa were both in February at 1.05 and 1.02, respectively. The size at first sexual maturity for female M. nepa was observed to be 100 mm in total length. The number of ova in females with mature ovaries was counted from 30 females and their mean fecundity was 425657.19 (± 18701.23) eggs. Bigger females have higher number of eggs. The identified prey items included seven major groups (decapod crustaceans,polychaetes, cephalopod molluscs, fish, gastropods and bivalves, eggs and unidentified items). Decapod crustaceans were the dominate prey items for M. nepa with an occurrence frequency and numerical abundance at 40.42 and 30.81 %, respectively. The occurrence frequency and numerical abundance were 19.28 and 27.35 % for polychaetes 9.69 and 6.18 % for cephalopod molluscs, 13.24 and 17.74% for fish, 4.90 and 4.58% for gastropods and bivalves, 0.28 and 3.16% for eggs and 3.85 and 1.85% for unidentified items, respectively. The maximum percentage and numerical abundance of each prey item changed at different months. Miyakella nepa was shown to be predatory carnivore, feeding mainly on the littoral zone communities. The mean total lengths for male and females were 122.89 (± 0.60) mm and 127.60 (± 061) mm,respectively indicating females were 4.71 mm longer compared to males. The estimated b value of M. nepa for both sexes in the present study (2.919) was similar to the isometric value (3). This indicates an isometric growth pattern of M. nepa in the coastal waters of Pantai Remis, Perak. For both sexes, fishing mortalities (F) was 2.84 compared to natural mortalities (M) of 0.62 indicating the balance position in the stock. The recruitment pattern for M. nepa was continuous with two major peaks per year. The exploitation rate (E) was 0.82 for combined sexes of M. nepa, and was higher than the E10 and E50 values of 0.79 and 0.43, respectively. Based on the fishing mortalities, and from the relative yield-per-recruit (Y/R), this indicates that M. nepa fishery is over exploited in the coastal waters of Pantai Remis, Perak. A more detailed study on this particular species would improve fisheries activities and stock assessment of M. nepa in the coastal waters of Malaysia.